Methyl jasmonate effects on Lactuca serriola L.: Antioxidant defense and bioactive compound changes: MeJA effects on Lactuca serriola - Asheri, Maisa; Farokhzad, Alireza; Naghavi, Mohammad Reza; Ghasemzadeh, Raheleh; Azadi, Pejman; Zargar, Meisam (Cellular and Molecular Biology, 2024)
The effect of methyl jasmonate (MeJA) foliar spray on the activity of antioxidant enzymes—Superoxide dismutase (SOD), Catalase (CAT), Ascorbate peroxidase (APX), and Guaiacol peroxidase (GPX)—along with assessments of total phenolic and flavonoid contents and antioxidant activity (IC50), was examined in Prickly lettuce (Lactuca serriola L.). The study involved treating plants with three MeJA solutions (0, 200, and 400 µM) and harvesting samples at four distinct time intervals. Varied MeJA concentrations and time intervals resulted in a substantial increase in the activity of all the antioxidant enzymes investigated in this study. Both concentration levels and time courses exhibited progressive outcomes. Moreover, MeJA treatment led to elevated levels of total phenolic and flavonoid contents, reaching peaks of 17.02 (mg GAL/g DW) and 8.3 (mg QUE/g DW), respectively, particularly in response to the 400 µM concentration. However, the total flavonoid content did not show any significant variation between the two concentrations. Based on the half-maximal inhibitory concentration (IC50) values, the antioxidant activity in MeJA-treated plants was found to be lower compared to the controls. However, our findings suggest that, under specific conditions discussed in this study, MeJA has the potential to enhance the nutritional value of L. serriola.